Anticancer activity of RM-3-22: a TAZQ-based hydroxamic acid derivative targeting NSCLC in vitro and in vivo - Chatterjee, Essha; Sharma, Ram; Dey, Biswajit; Singh, Hoshiyar; Naik, Aliva; Khan, Anjesh; Basak, Santanu; Bansode, Ankush; Sachdeva, Ritika; Sharma, Anamika; Kumar, Rahul; Naik, Pradeep; et al. (Frontiers in Pharmacology, 2025)
IntroductionLung cancer remains the leading cause of cancer-related deaths, necessitating novel therapeutic strategies. In this study, we developed RM-3-22, a TAZQ-based hydroxamic acid derivative with histone deacetylase (HDAC) inhibitory properties. We evaluated its anticancer activity in non-small cell lung cancer (NSCLC), using A549 adenocarcinoma cells as the primary model.MethodsThe anticancer efficiency of RM-3-22 was assessed in 2D and 3D cell culture models. Cell survivalism was analysed by MTT assay. Different microscopical staining methods, including acridine orange and DAPI, were employed to evaluate autophagy, nuclear changes, and apoptosis. Cell cycle progression, mitochondrial membrane potential, and apoptosis-necrosis profiles were assessed using flow cytometry. Protein and gene expression related to the RM-3-22 induced pathway were evaluated via immunofluorescence (IF), Western blotting, and RT-PCR. Functional gene analysis was performed using siRNA-mediated knockdown. Different in silico studies were also conducted to check the clinical relevance and expression pattern of the RM-3-22-induced gene. Additionally, the in vivo efficiency of the molecule was evaluated using the NOD/SCID xenograft model.ResultsRM-3-22 potentially suppressed cell viability and decreased the tumor spheroid size of A549s in vitro. It induced autophagy via downregulation of PI3K/Akt/mTOR signalling pathway. Besides, flow cytometry confirmed increased apoptotic cell population and decreased mitochondrial membrane potential due to the exposure of RM-3-22. RM-3-22 also promoted G2/M arrest. Signalling cascade confirmed that autophagy regulates RM-3-22-mediated apoptosis and cell cycle arrest. Additionally, RM-3-22 upregulated FTH1, a tumor suppressor, reinforcing its anticancer potential. Notably, RM-3-22 exhibited lower toxicity to normal cells, underscoring its selectivity. In vivo, RM-3-22 markedly reduced tumor growth in the xenograft mouse model.ConclusionRM-3-22 demonstrates potent anticancer activity through different mechanisms, including inhibition of the PI3K/Akt/mTOR pathway and activation of autophagy, apoptosis, and cell cycle arrest. Further, in vivo validation also supports that RM-3-22 represents a promising therapeutic candidate against lung cancer.